Systematic Groups of Soils of the Fergana Valley - Hamidov Abdusamad Abdumalikovich (Central Asian Journal of Theoretical and Applied Science, 2022)
In this article, the geographical distribution of soils in the Fergana Valley is divided into co-groups along with system equipment.